Persepsi Siswa Tentang Pelaksanaan Bimbingan dan Konseling di Sekolah Menengah Atas - Kamil, Badrul; Ilham, Pendi (Universitas Islam Negeri Raden Intan Lampung, 2015)
Perceptions of students SMA Negeri Pesisir Tengah generally do not have an understanding of Integral Counseling Guidance. There are three groups of opinions in perceiving counseling guidance (BK), First, students who perceive that counseling guidance (BK) as a disciplinary supervisor of students against school rules besides other problems. Secondly, counseling guidance (BK) as an effort to assist students in handling problems, especially the problem of discipline of students to the discipline of school, and Third, students who understand the BK as a guiding student guide and guide students, to help students understand themselves and help solve problems faced by students to better, Including discipline. In general, students' understanding of Counseling Guidance is as a student security handling body. As for the principles that exist in the Counseling Guidance in the process of activity is not yet understood. Thus, in the student's program, the target of counseling service in the activity process has not been fulfilled. Thus in the student's understanding, the target of counseling services or students relating to Counseling and Guidance are students who have school problems.